Kazakhstan and the European Union: Prospects of Cooperation in Developing the Agro-industrial Sector of Economy - MOLDAKENOVA, Yerkezhan; BAKIRBEKOVA, Aigul; MOLDASHBAYEVA, Luiza; BIYEV, Vilen; YSKAK, Nazira (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The basic goal of this research is to define top priority areas of the innovational partnership of the Republic of Kazakhstan with countries of the European Union in the development of the agro-industrial sector of economy. The analysis of the current state of the agro-industrial complex of the Republic of Kazakhstan gives evidences about the comparatively low efficiency of agriculture and low level of the food and processing industry development. The research made within this article says about serious problems decreasing the competitiveness of the agro-industrial complex of the Republic of Kazakhstan, for example, low innovational activity of Kazakh enterprises, limited access of individual farms and households to agricultural education, research and development and services related to distributing knowledge and experience, and the low level of investments in the development of agricultural innovations, etc. The results of the conducted research enabled the author to make conclusions about the further development of the agro-industrial complex of the Republic of Kazakhstan and its transfer to an essentially new technical and technological level. The author has come to the conclusion that the most important condition of the innovational development of the agro-industrial complex of the Republic of Kazakhstan is the expansion of cooperation related to developing organic agriculture, implementing joint international projects on stable development of the agro-industrial complex, and formation and development of the innovational infrastructure in the Republic of Kazakhstan.